Canaliculitis in supernumerary puncta and canaliculi - Ku Chui, Yong; Tan, Aik Kah; Faridah Hanom, Annuar (Licensee PAGEPress, Italy, 2011)
We report the first case of supernumerary puncta and canaliculi presented with canaliculitis. A-59 year-old gentleman presented with painful swelling of the left lower lid for a week, which was associated with epiphora. The swelling was confined to the nasal aspect of the left lower lid (0.5¥0.5 mm) with inflamed overlying skin. Two puncta (0.5 mm apart) were noted. The outer punctum at the normal anatomical position was a cul-de-sac while the inner punctum it the caruncle was patent. We described the embryology leading to supernumerary puncta and canaliculi to explain the paradoxical patency of the abnormally located punctum as well as the pathomechanism leading to canaliculitis. The patient was treated with oral cloxacillin 500 mg, 6 hourly for 5 days; the cellulitis subsided after three days.